Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7717/peerj.14208
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of G6PD deficiency and G6PD variants amongst the southern Thai population

Abstract: Background Glucose-6-phosphate dehydrogenase (G6PD) is an enzyme essential for NADPH production and protecting cells, especially red blood cells, from free radicals. The oxidative stress from drugs, chemicals, and infections can induce red blood cell hemolysis in G6PD deficiency patients, causing a genetic disorder. Objectives This study aims to provide more information on G6PD deficiency prevalence and the G6PD variants in the southern Thai population. Methods Five hundred and twenty healthy subjects in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, we are a region with a high prevalence of thalassemia, moreover, hemolysis and anemia are common ( Lin et al, 2015 ). Medication, hemolysis, and anemia can affect the detection of G6PD activity ( Nuinoon et al, 2022 ; Pfeffer et al, 2022 ). In our study, these may be one of the reasons that the 165 samples with no detection of any of the 33 common mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we are a region with a high prevalence of thalassemia, moreover, hemolysis and anemia are common ( Lin et al, 2015 ). Medication, hemolysis, and anemia can affect the detection of G6PD activity ( Nuinoon et al, 2022 ; Pfeffer et al, 2022 ). In our study, these may be one of the reasons that the 165 samples with no detection of any of the 33 common mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Using DiaplexC G6PD genotyping kit (Asian type), they identified G6PD Mahidol and G6PD Viangchan with the frequency of 0.5% and 0.4% in vivax malaria patients (n = 545). Another study in healthy volunteers revealed that the prevalence of G6PD deficiency in southern Thailand was approximately 8% (42/520) and Yala province has G6PD deficiency of 3.33% (1/30) [ 64 ]. Thus, our results suggest that screening for G6PD deficiency prior to 8-aminoquinoline therapy is necessary in this region to avoid unexpected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, approximately over 500 million people worldwide are affected by G6PD deficiency. Nonetheless, there are significant regional and ethnic variations in the prevalence of G6PD deficiency, ranging from 0% in the indigenous American inhabitants to more than 20% in some areas of Africa and Asia ( Arain and Bhutani, 2014 ; Galatas et al, 2017 ; Nuinoon et al, 2022 ). Epidemiologically, G6PD deficiency is more prevalent in the populations of southern China, particularly in the Guangdong ( Liang et al, 2022 ), Guangxi ( Yan et al, 2006 ), Hainan ( Zeng et al, 2022 ), and Jiangxi ( Liu et al, 2020 ) provinces.…”
Section: Introductionmentioning
confidence: 99%